ROLE OF MAGNETIC RESONANCE IMAGING IN THE STUDY OF PATIENTS WITH DIABETIC FOOT SYNDROME - M. A. Zamyshevskaya; V. D. Zavadovskaya; V. D. Udodov; M. A. Zorkal’tsev; E. G. Grigor’ev (Вестник рентгенологии и радиологии)
Objective: to give the results of magnetic resonance imaging (MRI) in patients with complicated diabetic foot syndrome (DFS) to rule out or identify osteomyelitis.Material and methods. Twenty-seven (14 women and 13 men; mean age 60±12.2 years) with type 1 and 2 diabetes mellitus and suspected osteomyelitis that had developed in the presence of DFS were examined. Ankle joint and foot MRI was carried out in T1-weighted MR image, T2-weighed MRI image, and FSat sequences. The soft tissue, tendoligamentous apparatus, and bones were evaluated. The results of MRI were compared with the data of a clinical follow-up study and surgery, followed by morphological examination. The diagnosis of osteomyelitis was validly established in 7 cases; this disease was absent in 20 patients.Results. MRI showed the highest sensitivity for bone marrow edema (100%), soft tissue swelling (85.7%), and their concurrence (85.7%) and the highest specificity for an extensive wound defect or fistula attached to the bone (100%) and bone marrow edema concurrent with tenosynovitis (90%). With a sensitivity of 14.3% and a specificity of 10%, MRI was of less informative value in assessing bone destruction. It was characterized by moderate sensitivity and moderate specificity for soft tissue destruction (57.1 and 42.9%, respectively) and tenosynovitis (55 and 50%, respectively).Conclusion. Osteomyelitis MRI demonstrated a polymorphic pattern with different diagnostic efficiency for individual symptoms.